Números figurados e as sequências recursivas : uma atividade didática envolvendo números triangulares e quadrados - Chiconello, Luis Alexandre (2013)
The shortage of activities regarding recursive defined sequences, allied to the importance of this theme to young students has been contested in at least twenty years of experience teaching Mathematics. The elaboration of a learning product, in a form of sheets of activities which gradually lead the student to the understanding of the concept of recursion, the pattern recognition, conjectures tests and formulas acquisition, could be inferred by the application of these sheets of activities in two high school classrooms in a technical state school. The data attained from these activities applications were analyzed and compared to the previously formed hypothesis (previous analysis) which were formed during the elaboration of the sheets of activities. The investigation method used was the Didactical Engineering. The students did the activities in groups of two or three students .They were participative and felt challenged in doing every step (lessons) proposed in the sheets. It was verified that the teaching material developed works, as it reached its main goals, the biggest one, the students learning. It is believed that the material developed may be useful to other teachers who may wish to develop the theme proposed in their classrooms, even adapting them to their students needs. This work brought to this author a great profession evolution which began with the theme choice, passed through the development of the material, the application in the classes and finally in the reflection of everything that was done and that is recorded in these notes.